2018
DOI: 10.1155/2018/1708272
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of Interdisciplinary Hip Fracture Rehabilitation in Frail Elderly Inpatients

Abstract: Objective To investigate short-term outcomes of an interdisciplinary rehabilitation program for elderly inpatients who underwent surgical treatment for hip fractures. Methods This is a prospective cohort study of fifty older inpatients who were admitted to a geriatric rehabilitation unit. Clinical and functional outcomes were assessed at admission, at discharge, and one month postdischarge. Results Patients mean age was 84.1 ± 4.7 years. Proportions of study population with risk factors of frailty were cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Reviews were deemed relevant if they reported the prevalence of malnutrition and its associations in hip fracture patients, but these reviews included studies that used nonestablished nutrition assessment tools. Where studies needed further clarity on whether it meets the inclusion criteria (ie, type of nutrition assessment tool used, if the diagnosis of malnutrition in patients was conducted within 48 h of hospital admission, and if patients were identical between studies), authors were contacted to minimize the unnecessary exclusion of studies 33–48 . Studies were excluded from our review if the authors did not respond.…”
Section: Methodsmentioning
confidence: 99%
“…Reviews were deemed relevant if they reported the prevalence of malnutrition and its associations in hip fracture patients, but these reviews included studies that used nonestablished nutrition assessment tools. Where studies needed further clarity on whether it meets the inclusion criteria (ie, type of nutrition assessment tool used, if the diagnosis of malnutrition in patients was conducted within 48 h of hospital admission, and if patients were identical between studies), authors were contacted to minimize the unnecessary exclusion of studies 33–48 . Studies were excluded from our review if the authors did not respond.…”
Section: Methodsmentioning
confidence: 99%
“…A study of patients in a geriatric rehabilitation unit also showed that the patients’ walking function improved with a shorter length of stay, but this may be because the patients whose walking function improved at an early phase were discharged with a shorter length of stay. 27 ) We could not evaluate the cognitive function of the present patients, but it has been reported that (i) cognitive function was not a significant factor in predicting unassisted walking among individuals with stroke, and (ii) only balance function was a significant factor. 28 ) The prediction of walking independence at discharge using only the BBS score at admission could therefore be sufficient, but cognitive function may have an effect on the classification from independent walking to outdoor walking and/or on the speed of walking.…”
Section: Discussionmentioning
confidence: 78%
“…16 Selain untuk deteksi bakteremia, CRP juga digunakan untuk justifikasi penggunaan antibiotik. 17 Masa rawat inap kelompok subjek usia lanjut yang lima hari lebih panjang dapat dikaitkan dengan 26 19 Selain itu, komorbiditas pada pasien usia lanjut juga pada umumnya lebih banyak dari pada dewasa muda sehingga interaksi antarberbagai kondisi tersebut dapat memengaruhi status fungsional yang pada gilirannya dapat mengakibatkan rerata lama rawat pasien usia lanjut lebih panjang. 20 Pasien yang dirawat dengan jaminan kesehatan nasional menggunakan skema paket INA-CBG yang telah ditetapkan sebelumnya; dengan demikian makin pendek masa rawat seseorang maka semakin efisien penggunaan sumber daya.…”
Section: Diskusiunclassified